2016
DOI: 10.1093/bioinformatics/btw237
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of hybrid and non-hybrid methods for de novo assembly of nanopore reads

Abstract: Supplementary data are available at Bioinformatics online.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(32 citation statements)
references
References 26 publications
1
31
0
Order By: Relevance
“…Typical examples of hybrid assemblers are ALLPATHS-LG [51], Celera Assembler’s PacBio corrected reads pipeline (pacBioToCA [52]), SPAdes [53], and SSPACE-LongRead [32]. Assessment and evaluation on these hybrid methods have been reported by Utturkar et al [54], Liao et al [55], and Sović et al [56]. ALLPATHS-LG takes a unique approach, in that, in addition to long reads, it also incorporates Illumina paired-end reads of two libraries: one with short overlapped fragments, and one with long jumps.…”
Section: Hybrid Assemblersmentioning
confidence: 99%
See 1 more Smart Citation
“…Typical examples of hybrid assemblers are ALLPATHS-LG [51], Celera Assembler’s PacBio corrected reads pipeline (pacBioToCA [52]), SPAdes [53], and SSPACE-LongRead [32]. Assessment and evaluation on these hybrid methods have been reported by Utturkar et al [54], Liao et al [55], and Sović et al [56]. ALLPATHS-LG takes a unique approach, in that, in addition to long reads, it also incorporates Illumina paired-end reads of two libraries: one with short overlapped fragments, and one with long jumps.…”
Section: Hybrid Assemblersmentioning
confidence: 99%
“…Evaluation of assembly methods and tools is difficult as the nanopore sequencing platform is still in the early stages of development and data sources are limited. Sović et al [56] has presented a comparison report on hybrid and non-hybrid methods for de novo assembly from MinION E . coli reads.…”
Section: Hybrid Assemblersmentioning
confidence: 99%
“…Nevertheless, although there is a constant development of new softwares applicable to ONT platforms, we found that the few evaluation studies made for nanopore-based shotgun sequencing data have focused on reconstructing single bacterial genomes from isolates, but not metagenomes (Goldstein et al, 2019;Tyler et al, 2018;Sović et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…GraphMap, like BLASR, was designed primarily as a read mapping tool (Sović et al , 2016), but for ONT data. It specifically addresses the overlap detection problem, notably producing full alignments.…”
Section: Long Read Overlap Methodologiesmentioning
confidence: 99%